Role of surfactin from Bacillus subtilis in protection against antimicrobial peptides produced by Bacillus species - Eyeghe-Bickong, Hans Andre (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2011.